Spurring Economic Growth in Terms of Happiness, Human Development, Competitiveness and Global Innovation: the ASEAN Case - Saida Zainurossalamia ZA; Siti Amalia; Dio Caisar Darma; Musdalifah Azis (ASEAN Journal on Science and Technology for Development, 2021)
Happiness, human development, level of competitiveness, and capacity in innovation all play an important role in spurring long-term sustainable economic growth. This study presents the relationship between these factors—happiness, human development, competitiveness, and innovation in the ASEAN region—in how they influence economic growth. To date, there has been a lack of research on this specific issue, and thus it is an interesting and little-known one to study. Panel data were used comprising a combination of time series and cross-sections. The object of the study was ASEAN member countries using the multiple linear regression method. For the years of 2013–2019, we found that overall economic growth had a real impact. The results showed that human development and global innovation are two-way related to economic growth (positive and significant). Conversely, there was an insignificant influence of happiness and competitiveness on economic growth. Competitiveness, in particular, can reduce the level of economic growth. The policy considerations pursued by countries in ASEAN are through the respective governments’ strategic steps to improve the productivity of their populations, because human resources are needed not only as objects but actors in economic activities themselves in managing development.